Multiple brace root phenotypes promote anchorage and limit root lodging in maize. (22nd February 2022) - Hostetler, Ashley N.; Erndwein, Lindsay; Reneau, Jonathan W.; Stager, Adam; Tanner, Herbert G.; Cook, Douglas; Sparks, Erin E.
Abstract: Plant mechanical failure (lodging) causes global yield losses of 7%−66% in cereal crops. We have previously shown that the above‐ground nodal roots (brace roots) in maize are critical for anchorage. However, it is unknown how brace root phenotypes vary across genotypes and the functional consequence of this variation. This study quantifies the contribution of brace roots to anchorage, brace root traits, plant height, and root lodging susceptibility in 52 maize inbred lines. We show that the contribution of brace roots to anchorage and root lodging susceptibility varies among genotypes and this contribution can be explained by plant architectural variation. Additionally, supervised machine learning models were developed and show that multiple plant architectural phenotypes can predict the contribution of brace roots to anchorage and root lodging susceptibility. Together these data define the plant architectures that are important in lodging resistance and show that the contribution of brace roots to anchorage is a good proxy for root lodging susceptibility. Summary statement: Root lodging is detrimental to crop yields, but the features of root systems that contribute to plant anchorage and limit root lodging are poorly defined. This study shows that the contribution of maize brace roots to anchorage and root lodging resistance is established through multiple plant traits.